Bearing-Only Formation Control for Cascade Multirobots - Qing Han (Mathematical Problems in Engineering, 2016)
A new formation control method is proposed, which is used to queue multirobots in a single-direction cascade structure. In the cascade formation, each robot is a follower for the previous robot and a leader for the next robot, and the robots in the middle act as both leader and follower. The follower robot can only observe the bearing information of the leader robot. The observability of the cascade leader-follower formation is studied, which shows that the bearing-only observation meets the observability conditions required for the nonlinear system. Based on the bearing-only observations, the unscented Kalman filter (UKF) is employed for the state estimation of the leader and the follower robots at all levels, which enables the real-time movement control of the follower robots via the input-output feedback control. Simulation results demonstrate that the proposed approach can efficiently control the formation of multirobots as desired.